2019
DOI: 10.1371/journal.pone.0219491
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and outcomes of a multi-function mobile health approach for the schizophrenia spectrum: App4Independence (A4i)

Abstract: Relative to the large investments in mobile health (mHealth) strategies for mental illnesses such as anxiety and depression, the development of technology to facilitate illness self-management for people with schizophrenia spectrum illnesses is limited. This situation falls out of step with the opportunity mHealth represents for providing inexpensive and accessible self-care resources and the routine use of mobile technologies by people with schizophrenia. Accordingly, the focus of this study was upon the feas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 30 publications
(47 reference statements)
2
57
2
7
Order By: Relevance
“…The finding that 43% of participants were willing to participate in WeChat-based mHealth programs resonates with a WeChat use rate of 40.75% among PLS in the current study. This rate was higher than that reported in other studies about online mental health program through social medias in and out of China ( Borzekowski et al, 2009 ; Kidd et al, 2019 ; Miller et al, 2015 ). For instance, Borzekowski et al reported only one third of PLS and people with other serious mental illness used internet for health information ( Borzekowski et al, 2009 ).…”
Section: Discussioncontrasting
confidence: 70%
“…The finding that 43% of participants were willing to participate in WeChat-based mHealth programs resonates with a WeChat use rate of 40.75% among PLS in the current study. This rate was higher than that reported in other studies about online mental health program through social medias in and out of China ( Borzekowski et al, 2009 ; Kidd et al, 2019 ; Miller et al, 2015 ). For instance, Borzekowski et al reported only one third of PLS and people with other serious mental illness used internet for health information ( Borzekowski et al, 2009 ).…”
Section: Discussioncontrasting
confidence: 70%
“…No Penulis/negara Metode Kondisi N Nama aplikasi/web Fitur aplikasi/web dan program intervensi 1 Xu D et al (19) Cina Fitur data demografi klien Fitur randomisasi responden berdasarkan data demografi, hasil randomisasi akan dikirimkan via email ke responden Fitur pengisian kuesioner Early Warning Sign (EWS) melalui telepon genggam klien dan keluarga Apabila hasil kuesioner menunjukkan adanya keparahan gejala maka email secara otomatis akan terkirim ke petugas yang merawat Klien dianjurkan mengunjungi pelayanan kesehatan dan akan diberikan tambahan terapi 3 Gottlieb JD et al (21) USA Fitur pengkajian early warning sign pada kekambuhan untuk menilai kekambuhan pada klien yang mendapatkan intervensi 1 tahun pengurangan dosis terapi antipsikotik 9 Kidd SA et al (27) Kanada (31) Cina…”
Section: Tabel 1 Karakteristik Artikel Pencegahan Kekambuhan Klien Sunclassified
“…(19,31) Fitur integrasi yang disediakan oleh aplikasi App4Independence hampir sama dengan LEAN dimana data kondisi kesehatan mental klien terintegrasi secara langsung dengan sistem informasi kesehatan sehingga petugas kesehatan dapat memantau keadaan klien dari jarak jauh. (27) M-Resist menggunakan web based platform sebagai alat untuk mengumpulkan data klien, dan melakukan komunikasi dan koordinasi dengan klien dan petugas kesehatan lainnya. (30)…”
Section: Integrasi Antara Klien Keluarga Dan Petugas Kesehatanunclassified
“…In this initial pilot, we focused on the early-stage testing of a digital health tool, App4Independence (A4i), which was performed in 2 steps. Following a preliminary 1-week beta test by 5 individuals to address technical issues, the qualitative and quantitative A4i outcome data from 38 individuals were analyzed, assessing feasibility over a 1-month period [ 32 ]. The mean number of interactions with the app per day was 4.21 and, by day 20, a 4% churn rate was observed (rates of individuals who ceased app use).…”
Section: Introductionmentioning
confidence: 99%